Communication in Transactive Memory Systems: A Review and Multidimensional Network Perspective. (February 2021) - Yan, Bei; Hollingshead, Andrea B.; Alexander, Kristen S.; Cruz, Ignacio; Shaikh, Sonia Jawaid
The comprehensive review synthesizes 64 empirical studies on communication and transactive memory systems (TMS). The results reveal that (a) a TMS forms through communication about expertise; (b) as a TMS develops, communication to allocate information and coordinate retrieval increases, promoting information exchange; and (c) groups update their TMS through communicative learning. However, direct interpersonal communication is not necessary for TMS development or utilization. Nor do high-quality information-sharing processes always occur within developed TMS structures. For future research, we propose a multidimensional network approach to TMS that incorporates technologies, addresses member characteristics, considers multiple communication types, and situates groups in context.